Phase I/II trial of vorinostat and radiation and maintenance vorinostat in children with diffuse intrinsic pontine glioma: A Children's Oncology Group report. Issue 4 (4th August 2021) - Su, Jack M; Kilburn, Lindsay B; Mansur, David B; Krailo, Mark; Buxton, Allen; Adekunle, Adesina; Gajjar, Amar; Adamson, Peter C; Weigel, Brenda; Fox, Elizabeth; Blaney, Susan M; Fouladi, Maryam
Abstract: Background: A phase I/II trial of vorinostat (suberoylanilide hydroxamic acid), an oral histone deacetylase inhibitor, was conducted in children with newly diagnosed diffuse intrinsic pontine glioma (DIPG) through the Children's Oncology Group (COG) to: 1) determine the recommended phase II dose (RP2D) of vorinostat given concurrently with radiation therapy; 2) document the toxicities of continuing vorinostat as maintenance therapy after radiation; and 3) to determine the efficacy of this regimen by comparing the risk of progression or death with a historical model from past COG trials. Methods: Vorinostat was given once daily, Monday through Friday, during radiation therapy (54 Gy in 30 fractions), and then continued at 230 mg/m 2 daily for a maximum of twelve 28-day cycles. Results: Twelve patients enrolled in the phase I study; the RP2D of vorinostat given concurrently with radiation was 230 mg/m 2 /day, Monday through Friday weekly. The six patients enrolled at the RP2D and an additional 64 patients enrolled in the phase II study contributed to the efficacy assessment. Although vorinostat was well-tolerated, did not interrupt radiation therapy, and was permanently discontinued in only 8.6% of patients due to toxicities, risk for EFS-event was not significantly reduced compared with the target risk derived from historical COG data ( P = 0.32; 1-sided). The 1-year EFS was 5.85% (95% CI 1.89–13.1%) and 1-year OS was 39.2% (27.8–50.5%). Conclusions: Vorinostat given concurrently with radiation followed by vorinostat monotherapy was well tolerated in children with newly diagnosed DIPG but failed to improve outcome.